FCAM: COMBINATION OF FLIPPED-CLASSROOM APPROACH AND MULTIMODALITY FOR LEARNING PRODUCTIVE SKILLS ONLINE - Valentina Dyah Arum Sari; Heribertus Binawan (JISOS: JURNAL ILMU SOSIAL, 2022)
Online learning provides many changes, expects adaptation and creates a new concern and order in the world of education. A new term, FCAM (Flipped Classroom Approach and Multimodality) was be applied in this online learning process, especially the focus in this study is productive skills. The study was conducted through mixed-method research by distributing questionnaire and doing the interview to the participants. The research results revealed that the FCAM gained a positive response from the students for helping the learning productive skill in Speaking Class. FCAM implementation achieved 61,78% as the responses form the students. The FCAM implementation was in medium qualification. The students shared their thoughts about the FCAM implementation and they were satisfied to have this teaching and learning strategies. However, there were several obstacles in the FCAM implementation from the students’ point of view including unstable internet connection that made the student could not optimally joining the Zoom meeting as the face-to-face learning and also as the completion stage of the FCAM itself